2021
DOI: 10.1159/000512063
|View full text |Cite
|
Sign up to set email alerts
|

Early Use of Corticosteroid May Prolong SARS-CoV-2 Shedding in Non-Intensive Care Unit Patients with COVID-19 Pneumonia: A Multicenter, Single-Blind, Randomized Control Trial

Abstract: <b><i>Background:</i></b> There is still no clinical evidence available to support or to oppose corticosteroid treatment for coronavirus disease 2019 (COVID-19) pneumonia. <b><i>Objective:</i></b> To investigate the efficacy and safety of corticosteroid given to the hospitalized patients with COVID-19 pneumonia. <b><i>Methods:</i></b> This was a prospective, multicenter, single-blind, randomized control trial. Adult patients with COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
159
2
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(167 citation statements)
references
References 27 publications
3
159
2
3
Order By: Relevance
“…This nding was supported by recent studies [2,40,41], in which corticosteroid therapy led to different clinical outcomes according to severity of illness. We speculated that the absence of bene t in the low CL group may be partially explained by the delayed viral clearance [42][43][44]. In the present study, patients in the low CL group receiving steroids had relatively longer viral shedding duration than those who were not receiving steroids, although the difference was not statistically signi cant.…”
Section: Discussioncontrasting
confidence: 51%
“…This nding was supported by recent studies [2,40,41], in which corticosteroid therapy led to different clinical outcomes according to severity of illness. We speculated that the absence of bene t in the low CL group may be partially explained by the delayed viral clearance [42][43][44]. In the present study, patients in the low CL group receiving steroids had relatively longer viral shedding duration than those who were not receiving steroids, although the difference was not statistically signi cant.…”
Section: Discussioncontrasting
confidence: 51%
“…All included studies had data regarding mortality. Of note, 1 study evaluated mortality at 30 days, [ 21 ] 3 studies evaluated mortality at 28 days, [ 16 18 ] 1 study evaluated mortality at 21 days, [ 15 ] 1 study evaluated mortality at 14 days, [ 19 ] and 2 studies did not specify a date for mortality (time of death). [ 20 , 22 ] Across all available studies, the overall mortality rate in the steroids group was 22.9% (95% CI: 13.0%; 37.1%), while the overall mortality rate for the SOC group was 31.0% (95% CI: 20.3%; 44.3%).…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies included in the quantitative meta-analysis, 5 had data regarding mechanical ventilation rates. [ 15 , 17 , 18 , 20 , 21 ] Across all available studies, the overall mechanical ventilation rate in the steroids group was 14.0% (95% CI: 5.6%; 30.4%), while the overall mechanical ventilation rate for the SOC group was 16.3% (95% CI: 4.6%; 44.3%). The need for mechanical ventilation in the steroids group was significantly lower compared to the SOC group (OR = 0.76 [95% CI: 0.59; 0.97], P = .030; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results in a retrospective study suggested corticosteroids were associated with delayed MERS coronavirus RNA clearance ( Arabi et al, 2018 ). Additionally, studies also showed corticosteroid use was associated with longer throat viral RNA detectability and acute respiratory syndrome coronavirus 2 shedding in mild-to-moderate COVID-19 patients, and clinical benefits on these patients were limited ( Jamaati et al, 2021 ; Tang et al, 2021 ). Immune response and CD8 + T cell infiltration were involved in the COVID-19 pathological process, and reduction of CD4 + T cells, CD8 + T cells, and NK cells was observed on day 7 after corticosteroid use ( Du et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%